2000
DOI: 10.1046/j.1365-2540.2000.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

F1 hybrid inviability in Eucalyptus: the case of E. ovata × E. globulus

Abstract: The impact of inbreeding and hybridization on fitness was compared in the two co‐occurring forest tree species, Eucalyptus ovata and E. globulus, aimed at explaining the rarity of their hybrids in nature. The success of selfing, open‐pollination and outcrossing of both species and interspecific hybridization was monitored from seed‐set to 10‐year’s growth in a field trial. There was a unilateral barrier to hybridization with seed‐set obtained only with E. ovata females. The F1 hybrids exhibited reduced viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 25 publications
3
61
2
Order By: Relevance
“…The phylogenetic relationships between the species affected hybridization success, with intraseries crosses producing more hybrid seedlings than interseries and intersectional crosses. Lopez et al (2000) found that in E. ovata # E. globulus hybrids, there was a significant reduction in hybrid fitness relative to the parents, with not only seedling deformity but also progressive mortality in young trees over time. This means that even though hybrids have been formed here and can be identified at early stages for further development, there is still no guarantee of their longterm survival, let alone horticultural merit.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The phylogenetic relationships between the species affected hybridization success, with intraseries crosses producing more hybrid seedlings than interseries and intersectional crosses. Lopez et al (2000) found that in E. ovata # E. globulus hybrids, there was a significant reduction in hybrid fitness relative to the parents, with not only seedling deformity but also progressive mortality in young trees over time. This means that even though hybrids have been formed here and can be identified at early stages for further development, there is still no guarantee of their longterm survival, let alone horticultural merit.…”
Section: Discussionmentioning
confidence: 98%
“…The long time to flowering can also make the morphological assessment of hybridity in offspring difficult or, at best, a long-term prospect, especially where there are longer-term problems with hybrid fitness and survival (Lopez et al 2000) or where the ratio of male to female parental dominance alternates within the first few years (Bouvet andVigneron 1995, 1996), although predictive parental contribution based on multivariate morphological assessments is possible for some features (Baril et al 1997a(Baril et al , 1997b. The current study found that at least for the seedling stage, the hybrid offspring with E. gillii as the mother were either intermediate or tended to resemble the mother (crosses with E. orbifolia and E. transcontinentalis), whereas nearly all the female E. socialis crosses showed apparent early maternal dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that both first-and advanced-generation hybrid breakdowns are common in Eucalyptus (Potts and Dungey 2003; and can be effective barriers to inter-specific gene flow (Potts and Wiltshire 1997). For example, F 1 hybrids between E. ovata and E. globulus, a species closely related to E. nitens, showed poor survival by flowering age, compared with the pure species (Lopez et al 2000b). Furthermore, while these two species overlap in their flowering time, the flowering of their F 1 hybrid does not overlap with either species (Lopez et al 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding depression is commonly observed in fitness related traits associated with survival, reproduction and growth, and is believed to arise through two main non-mutually exclusive mechanisms: firstly dominance, whereby inbreeding unmasks deleterious recessive or partially recessive alleles; and secondly, whereby inbreeding increases homozygosity at loci exhibiting overdominance (Charlesworth and Charlesworth, 1987;Lande and Schemske, 1985). From an evolutionary and conservation perspective, inbreeding depression is important as it will initially lower population fitness, resulting in a phase where small populations of normally outbred species are more susceptible to ecological or genetic displacement (Ellstrand and Elam, 1993;Lopez et al, 2000). However, such selection may eventually result in the purging of deleterious alleles from populations surviving bottlenecks (Klekowski, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This is certainly the case in the predominantly Australian genus Eucalyptus where, across the 23 species tested, outcrossing rates in the wild average 74% (Byrne, 2008;Potts and Wiltshire, 1997). The few eucalypt species studied to date have all shown significant inbreeding depression on traits related to fitness, not only following controlled selfing (Griffin and Cotterill, 1988;Hardner and Potts, 1995;Hardner and Tibbits, 1998;Lopez et al, 2000), but also in offspring derived from open-pollinated seed collected from the wild (see previous citations; Hodge et al, 1996;Volker, 2002). However, the limited number of founder parents used in these studies would limit their power for evaluating the effects of inbreeding, particularly on observational variance components.…”
Section: Introductionmentioning
confidence: 99%